Nanomaterials based biosensors applied for detection of aflatoxin B1 in cereals: a review - Loyce Namanya; Emma Panzi Mukhokosi; Ediriisa Mugampoza (Discover Materials)
Abstract Aflatoxin B1 (AFB1) is a highly strong mycotoxin that contaminates cereals and other stored grains. It causes immune-suppressive effects, raising the risk of mutagenicity, carcinogenicity, teratogenicity, hepatotoxicity, and embryonic toxicity, as well as increasing illness and death. Liver damage is a result of prolonged exposure to AFB1, which raises the prevalence of liver cancer and cirrhosis. Different biosensors have been fabricated using various nanoparticles to detect aflatoxins in food. This review provides the recent developments on the occurrence of AFB1 in cereals, different biosensors based on nanomaterials applied for AFB1 detection in cereals, and offers future directions for the production of affordable analytical equipment for detection of AFB1, based on nanomaterials to address some open questions regarding their limit of detection, stability, and affordability. Electrochemical biosensors are more reliable, selective, and affordable analytical tools with better detection limits and shorter response times than other biosensors. However, more studies are needed to address the automatic simultaneous detection of various aflatoxins in real samples and a biosensing system that integrates with microarray technology.